Impact Analysis of Rules of Origin on Indonesia Export Performance: Case Study on Indonesia-Japan - Andiani, Desy (Cendekia Niaga, 2024)
Japan is one of main Indonesia’s trading partners. This research aims to analyse the impact of ROO’s restrictiveness on the Indonesia export performance and the utilisation of preferential schemes for both IJEPA and AJCEP. This study constructs ROO Index based on Product Specific Rules (PSR), as proxy of ROO, at 6-digit HS level to measure the restrictiveness level. This research found that the restrictiveness of ROO has a negative impact on total exports and utilisation for both FTAs. Increasing rate of applied tariff would reduces the total export, while the rate of margin tariff positifely impacts the utilisation rate. Providing facilitative PSR would likely improve export performance and utilisation of international trade agreements.